0% found this document useful (0 votes)
21 views

Functions 1A

The document contains solutions to math problems involving function composition. It defines several functions and finds their compositions and inverses. Specifically, it finds (f o g), the composition of functions f and g, and the inverses f-1 and g-1 for various functions f and g. It also shows that (gof)-1 = f-1 o g-1 for certain bijective functions f and g.
Copyright
© © All Rights Reserved
Available Formats
Download as PDF, TXT or read online on Scribd
0% found this document useful (0 votes)
21 views

Functions 1A

The document contains solutions to math problems involving function composition. It defines several functions and finds their compositions and inverses. Specifically, it finds (f o g), the composition of functions f and g, and the inverses f-1 and g-1 for various functions f and g. It also shows that (gof)-1 = f-1 o g-1 for certain bijective functions f and g.
Copyright
© © All Rights Reserved
Available Formats
Download as PDF, TXT or read online on Scribd
You are on page 1/ 7

AP Board Solutions Class 10

AP Board Solutions Class 9

Intermediate 1st Year Maths 1A Functions Solutions Exercise 1(b)


I.

Question 1.
If f(x) = ex and g(x) = logex, then show that f o g = g o f and find f-1 and g-1.
Solution:
Given f(x) = ex and g(x) = logex
Now (f o g) (x) = f(g(x))
= f(logex) [∵ g(x) = logex]
= e(logex)
=x
∴ (fog) (x) = x ………(1)
and (g o f) (x) = g(f(x))
= g(ex) [∵ f(x) = ex]
= loge (ex) [∵ g(x) = logex]
= x loge (e)
= x(1)
=x
∴ (g o f) (x) = x …….(2)
From (1) and (2)
fog=gof
Given f(x) = ex
Let y = f(x) = ex ⇒ x = f-1(y)
and y = ex ⇒ x = loge (y)
∴ f-1(y) = loge (y) ⇒ f-1(x) = loge (x)
Let y = g(x) = loge (x)
∵ y = g(x) ⇒ x = g-1(y)
∵ y = loge (x) ⇒ x = ey
∴ g-1(y) = ey ⇒ g-1(x) = ex
∴ f-1(x) = loge (x) and g-1(x) = ex

Question 2.
If f(y) = y1−y2√, g(y) = y1+y2√ then show that (fog) (y) = y
Solution:
f(y) = y1−y2√ and g(y) = y1+y2√
Now, (fog) (y) = f(g(y))
∴ (fog) (y) = y

Question 3.
If f : R → R, g : R → R are defined by f(x) = 2x2 + 3 and g(x) = 3x – 2, then find
(i) (fog)(x)
(ii) (gof) (x)
(iii) (fof) (0)
(iv) go(fof) (3)
Solution:
f : R → R, g : R → R and f(x) = 2x2 + 3; g(x) = 3x – 2
(i) (f o g) (x) = f(g(x))
= f(3x – 2) [∵ g(x) = 3x – 2]
= 2(3x- 2)2 + 3 [∵ f(x) = 2x2 + 3]
= 2(9x2 – 12x + 4) + 3
= 18x2 – 24x + 8 + 3
= 18x2 – 24x + 11

(ii) (gof) (x) = g(f(x))


= g(2x2 + 3) [∵ f(x) = 2x2 + 3]
= 3(2x2 + 3) – 2 [∵ g(x) = 3x – 2]
= 6x2 + 9 – 2
= 6x2 + 7

(iii) (fof) (0) = f(f(0))


= f(2(0) + 3) [∵ f(x) = 2x2 + 3]
= f(3)
= 2(3)2 + 3
= 18 + 3
= 21

(iv) g o (f o f) (3)
= g o (f (f(3)))
= g o (f (2(3)2 + 3)) [∵ f(x) = 2x2 + 3]
= g o (f(21))
= g(f(21))
= g(2(21)2 + 3)
= g(885)
= 3(885) – 2 [∵ g(x) = 3x – 2]
= 2653

Question 4.
If f : R → R, g : R → R are defined by f(x) = 3x – 1, g(x) = x2 + 1, then find
(i) (f o f) (x2 + 1)
(ii) f o g (2)
(iii) g o f (2a – 3)
Solution:
f : R → R, g : R → R and f(x) = 3x – 1 ; g(x) = x2 + 1
(i) (f o f) (x2 + 1)
= f(f(x2 + 1))
= f[3(x2 + 1) – 1] [∵ f(x) = 3x – 1]
= f(3x2 + 2)
= 3(3x2 + 2) – 1
= 9x2 + 5

(ii) (f o g) (2)
= f(g(2))
= f(22 + 1) [∵ g(x) = x2 + 1]
= f(5)
= 3(5) – 1
= 14 [∵ f(x) = 3x – 1]

(iii) (g o f) (2a – 3)
= g(f(2a – 3))
= g[3(2a – 3) – 1] [∵ f(x) = 3x – 1]
= g(6a – 10)
= (6a – 10)2 + 1 [∵ g(x) = x2 + 1]
= 36a2 – 120a + 100 + 1
= 36a2 – 120a + 101

Question 5.
If f(x) = 1x, g(x) = √x for all x ∈ (0, ∞ ) then find (g o f) (x).
Solution:
f(x) = 1x, g(x) = √x, ∀ x ∈ (0, ∞ )
(g o f) (x) = g(f(x))
= g(1x) [∵ f(x) = 1x]
= 1x−−√
= 1x√ [∵ g(x) = √x]
∴ (gof) (x) = 1x√
Question 6.
f(x) = 2x – 1, g(x) = x+12 for all x ∈ R, find (g o f) (x).
Solution:
f(x) = 2x – 1, g(x) = x+12 ∀ x ∈ R
(g o f) (x) = g(f(x))
= g(2x – 1) [∵ f(x) = 2x – 1]
= (2x−1)+12
= x [∵ g(x) = x+12]
∴ (g o f) (x) = x

Question 7.
If f(x) = 2, g(x) = x2, h(x) = 2x for all x ∈ R, then find (f o (g o h)) (x).
Solution:
f(x) = 2, g(x) = x2, h(x) = 2x, ∀ x ∈ R
[f o (g o h) (x)]
= [f o g (h(x))]
= f o g (2x) [∵ h(x) = 2x]
= f[g(2x)]
= f((2x)2) [∵ g(x) = x2]
= f(4x2) = 2 [∵ f(x) = 2]
∴ [f o (g o h) (x)] = 2

Question 8.
Find the inverse of the following functions.
(i) a, b ∈ R, f : R → R defined by f(x) = ax + b, (a ≠ 0).
Solution:
a, b ∈ R, f : R → R and f(x) = ax + b, a ≠ 0
Let y = f(x) = ax + b
⇒ y = f(x)
⇒ x = f-1(y) ……..(i)
and y = ax + b
⇒ x = y−ba ……..(ii)
From (i) and (ii)
f-1(y) = y−ba
⇒ f-1(x) = x−ba
(ii) f : R → (0, ∞ ) defined by f(x) = 5x
Solution:
f : R → (0, ∞ ) and f(x) = 5x
Let y = f (x) = 5x
y = f(x) ⇒ x = f-1(y) ……(i)
and y = 5x ⇒ log5 (y) = x ……..(ii)
From (i) and (ii)
f-1(y) = log5(y) ⇒ f-1(x) = log5 (x)

(iii) f : (0, ∞ ) → R defined by f(x) = log2 (x).


Solution:
f : (0, ∞ ) → R and f(x) = log2 (x)
Let y = f(x) = log2 (x)
∵ y = f(x) ⇒ x = f-1(y) ……..(i)
and y = log2(x) ⇒ x = 2y
From (i) and (ii)
f-1(y) = 2y ⇒ f-1(x) = 2x

Question 9.
If f(x) = 1 + x + x2 + …… for |x| < 1 then show that f-1(x) = x−1x
Solution:
f(x) = 1 + x + x2 + ……..

Question 10.
If f : [1, ∞ ) ⇒ [1, ∞ ) defined by f(x) = 2x(x−1) then find f-1(x).
Solution:

II.

Question 1.
If f(x) = x−1x+1, x ≠ ±1, then verify (f o f-1) (x) = x.
Solution:
Given f(x) = x−1x+1, x ≠ ±1
Let y = f(x) = x−1x+1
∵ y = f(x) ⇒ x = f-1(y) ……(i)
and y = x−1x+1

Question 2.
If A = {1, 2, 3}, B = {α, β, γ}, C = {p, q, r} and f : A → B, g : B → C are defined by f = {(1, α), (2, γ),
(3, β)}, g = {(α, q), (β, r), (γ, p)}, then show that f and g are bijective functions and (gof)-1 = f-1 o
g-1.
Solution:
A = {1, 2, 3}, B = {α, β, γ},
f : A → B and f = {(1, α), (2, γ), (3, β)}
⇒ f(1) = α, f(2) = γ, f(3) = β
∵ Distinct elements of A have distinct f – images in B, f: A → B is an injective function.
Range of f = {α, γ, β} = B(co-domain)
∴ f : A → B is a surjective function.
Hence f : A → B is a bijective function.
B = {α, β, γ}, C = {p, q, r}, g : B → C and g : {(α, q), (β, r), (γ, p)}
⇒ g(α) = q, g(β) = r, g(γ) = p
∴ Distinct elements of B have distinct g – images in C, g : B → C is an injective function.
Range of g = {q, r, p} = C, (co-domain)
∴ g : B → C is a surjective function
Hence g : B → C is a bijective function
Now f = {(1, α), (2, γ), (3, β)}
g = {(α, q), (β, r), (γ, p)}
g o f = {(1, q), (2, p), (3, r)}
∴ (g o f)-1 = {(q, 1), (r, 3), (p, 2)} ………(1)
g-1 = {(q, α), (r, β), (p, γ)}
f-1 = {(α, 1), (γ, 2),(β, 3)}
Now f-1 o g-1 = {(q, 1), (r, 3), (p, 2)} …….(2)
From eq’s (1) and (2)
(gof)-1 = f-1 o g-1

Question 3.
If f : R → R, g : R → R defined by f(x) = 3x – 2, g(x) = x2 + 1, then find
(i) (g o f-1) (2)
(ii) (g o f)(x – 1)
Solution:
f : R → R, g : R → R and f(x) = 3x – 2
f is a bijective function ⇒ its inverse exists
Let y = f(x) = 3x – 2
∵ y = f(x) ⇒ x = f-1(y) …….(i)
and y = 3x – 2
⇒ x = y+23 ……..(ii)
From (i) and (ii)
f-1(y) = y+23
⇒ f-1(x) = x+23
Now (gof-1) (2)
= g(f-1(2))

∴ (g o f-1) (2) = 259


(ii) (g o f) (x -1)
= g(f(x – 1))
= g(3(x – 1) – 2) [∵ f(x) = 3x – 2]
= g(3x – 5)
= (3x – 5)2 + 1 [∵ g(x) = x2 + 1]
= 9x2 – 30x + 26
∴ (g o f) (x – 1) = 9x2 – 30x + 26

Question 4.
Let f = {(1, a), (2, c), (4, d), (3, b)} and g-1 = {(2, a), (4, b), (1, c), (3, d)} then show that (gof)-1 = f-
1 o g-1
Solution:
f = {(1, a), (2, c), (4, d), (3, b)}
∴ f-1 = {(a, 1), (c, 2), (d, 4), (b, 3)}
g-1 = {(2, a), (4, b), (1, c), (3, d)}
∴ g = {(a, 2), (b, 4), (c, 1), (d, 3)}
(g o f) = {(1, 2), (2, 1), (4, 3), (3, 4)}
∴ (gof)-1 = {(2, 1), (1, 2), (3, 4), (4, 3)} ……….(1)
f-1 o g-1 = {(2, 1), (4, 3), (1, 2), (3, 4)} ……..(2)
From eq’s (1) and (2), we observe (gof)-1 = f-1 o g-1
Question 5.
Let f : R → R, g : R → R be defined by f(x) = 2x – 3, g(x) = x3 + 5 then find (f o g)-1 (x).
Solution:
f : R → R, g : R → R and f(x) = 2x – 3 and g(x) = x3 + 5
Now (fog) (x) = f(g(x))
= f(x3 + 5) [∵ g(x) = x2 + 5]
= 2(x3 + 5) – 3 [∵ f(x) = 2x – 3]
= 2x3 + 7
∴ (f o g) (x) = 2x3 + 7
Let y = (f o g) (x) = 2x3 + 7
∵ y = (fog)(x)
⇒ x = (fog)-1 (y) …….(1)
and y = 2x3 + 7
⇒ x3 = y−72
⇒ x = (y−72)13 …..(2)
From eq’s (1) and (2),
(f o g)-1 (y) = (y−72)13
∴ (f o g)-1 (x) = (x−72)13

Question 6.
Let f(x) = x2, g(x) = 2x. Then solve the equation (f o g) (x) = (g o f) (x)
Solution:
Given f(x) = x2 and g(x) = 2x
Now (f o g) (x) = f(g(x))
= f(2x) [∵ g(x) = 2x]
= (2x)2
= 22x [∵ f(x) = x2]
∴ (f o g) (x) = 22x ……(1)
and (g o f) (x) = g(f(x))
= g(x2) [∵ f(x) = x2]
= (2)x2 [∵ g(x) = 2x]
∴ (g o f) (x) = (2)x2
∵ (f o g) (x) = (g o f) (x)
⇒ 22x = (2)x2
⇒ 2x = x2
⇒ x2 – 2x = 0
⇒ x(x – 2) = 0
⇒ x = 0, x = 2
∴ x = 0, 2

Question 7.
If f(x) = x+1x−1, (x ≠ ±1) then find (fofof) (x) and (fofofof) (x).
Solution:
f(x) = x+1x−1, (x ≠ ±1)
(i) (fofof) (x) = (fof) [f(x)]
= (fof) (x+1x−1) [∵ f(x) = (x+1x−1)]

(ii) (fofofof) (x) = f[(f o f o f) (x)]


= f [f(x)] {from (1)}

In the above problem if a number of f is even its answer is x and if a number of f is odd its
answer is f(x).

CategoriesInter 1st Year


Post navigation
Inter 1st Year Maths 1A Products of Vectors Formulas
AP Board 9th Class Physical Science Solutions 12th Lesson ప లు మ యు లు
Leave a Comment
Comment

NameEmailWebsite

Save my name, email, and website in this browser for the next time I comment.

Post Comment
Recent Posts
AP SSC 10th Class Physics Chapter Wise Important Questions and Answers 2021-2022
English & Telugu Medium
AP Board 6th Class Social Studies Textbook Solutions Study Material Guide
AP Board 7th Class Social Studies Textbook Solutions Study Material Guide
AP Board 7th Class Social Studies Important Questions and Answers English & Telugu
Medium
AP Board 6th Class Hindi Textbook Solutions Study Material Guide
AP Board 6th Class Maths Textbook Solutions Study Material Guide
AP Board 7th Class Science Important Questions and Answers English & Telugu Medium
AP Board 9th Class Textbook Solutions Study Material Guide
AP Board 10th Class Textbook Solutions Study Material Guide
AP Board 6th Class Textbook Solutions Study Material Guide
AP Board 7th Class Hindi Important Questions and Answers
Copyright © 2023 AP Board Solutions

You might also like